Nomads of the world - Bahmanbegui, Mohammad; Cole, Donald P.; De Munck, Alyette; Dyson-Hudson, Neville; Englebert, Victor; McIntyre, Loren; Nimmo, H. Arlo; Ruhela, Satya Pal; Carmichael, Leonard; Allen, William L. (National Geographic Society, 1971)
"Distinguished scholars write of the lives and customs of eight groups- Lohars of India, etc. who wander over long distances in search of food and water for their families and animals."